Teste de progresso: a percepção do discente de Medicina - Chinelato, Marlene Moraes Rosa (2018)
Objective: This descriptive research of qualitative approach aimed to analyze the students ' perception of the undergraduate course of Medicine of a University Center in the northwest Paulista about their performance in the progress test, as well as the impact of this perception in the short term and, from that, propose adjustments actions for the continuous improvement of the teaching-learning process.The sample of convenience was made up by twenty participants, after approval of the research at the Ethics Committee on Research. The technique of focal groups was applied in two distinct moments to collect the qualitative data. The content analysis of the focal groups was based on Bardin (2011). Results: Ten students of the fifth period took part in the first focal group and ten students of the eighth period took part in the second group. The analysis of the content of the interviews resulted in the identification of three categories:1. Inappropriate conditions; 2.PT as a pedagogical tool; 3. Antagonistic feelings. Conclusion: The students that were interviewed consider the ProgressTest a relevant "pedagogical tool" that allows self-assessment and correction of learning gaps.&n bsp; However, the performance results of PT and the received feedback determine antagonistic feelings according to the period they are taking, of frustration for the fifth period students and security for the students of the eighth period. The impact determined by the performance in the short-term PT did not promote changes in the study plan of the students that were interviewed. It is necessary to implement strategies for the delivery of the formative feedback in a reflexive way, which allows the discussion of the issues and the results of the course/classes enhancing the teaching-learning process